ظفار فى مصادر حضرموت التاريخية فى القرن العاشر الهجرى : قراءة تاريخية - الجعيدي, عبدالله سعيد سليمان (الندوة الدولية التبادل الحضاري العماني اليمني (7 - 8 فبراير 2010م) إعداد : مركز الدراسات العمانية, 2011)
Keywords: Dhofar

The Nubian Complex of Dhofar, Oman: An African Middle Stone Age Industry in Southern Arabia - Rose, Jeffrey I.; Usik, Vitaly I.; Marks, Anthony E.; Hilbert, Yamandu H.; Galletti, Christopher S.; Parton, Ash; Geiling, Jean Marie; Černý, Viktor; Morley, Mike W.; Roberts, Richard G. (PLoS ONE, 2011)
Despit e the numerous studies proposing early human population expansions from Africa into Arabia during the Late Pleistocene, no archaeological sites have yet been discovered in Arabia that resemble a specific African industly. which would indicate demographic exchange across the Red Sea. Here we report the discovery of a buried site and more than 100 new surface scatters in the Dhofar region of Oman belo ng ing to a regionally-specific African lithic industry- the late Nubian Complex - known previously only from the northeast and Horn of Africa during Marine Isotope Stage 5, - 128,000 to 74,000 years ago. Two optically stimulated luminescence age estimates from the open-air site of Aybut AI Auwal in Oman place the Arabian Nubian Complex at - 106,000 years ago, providing archaeological evidence for the presence of a distinct northeast African Middle Stone Age technocomplex in southern Arabia sometime in the first half of Marine Isotope Stage 5.
Keywords: Dhofar

Military Intelligence, Tribes, and Britain's War in Dhofar, 1970–1976 - Jones, Clive (Middle East Journal, 2011)
Keywords: Dhofar